The Effectiveness of Integrated Comic Electronic Media Islamic Values on Students' Creative Thinking Ability - Ucca Swasti Praptiwi; Agus Yulianto; Ellianawati Ellianawati (Postgraduate, University of Mataram, 2021)
Learning activities that utilize digital technology for online learning are an alternative during the COVID-19 pandemic. This study aims to determine the effectiveness of electronic comic media based on problem-based learning integrated with Islamic values to improve students' creative thinking skills. This study uses a Research and Development approach using the ADDIE model. The subjects in the study were 90 students of class VIII. Data collection techniques using research instruments with quantitative data analysis. The data collection instrument was by giving essay questions in the form of a creative thinking ability test. The study of creative thinking skills by calculating the N-gain and the significance test was carried out using an average difference test through a t-test with the help of SPSS. The results showed that the value of significance (2 tailed) from the two schools, namely 0.00 < 0.05, then H0 is rejected, and Ha is accepted, so it can be concluded that there is a difference in the average creative thinking ability of the pretest and posttest both at SMP N 3 Watumalang and at SMP IT Permata Hati, which means that there is an effect of using E-Comic media in improving students' creative thinking skills